(Hexafluoroacetylacetonato)copper(i)–cycloalkyne complexes as protected cycloalkynes. Issue 77 (27th August 2020) - Makio, Naoaki; Sakata, Yuki; Kuribara, Tomoko; Adachi, Keisuke; Hatakeyama, Yasutomo; Meguro, Tomohiro; Igawa, Kazunobu; Tomooka, Katsuhiko; Hosoya, Takamitsu; Yoshida, Suguru
Abstract : Protection method of cycloalkynes by forming (hexafluoroacetylacetonato)copper(i )–cycloalkyne complexes is disclosed. Selective click reactions are realized through the complexation of cycloalkynes with copper. Abstract : A protection method for cycloalkynes by the formation of (hexafluoroacetylacetonato)copper(i )–cycloalkyne complexes is disclosed. Various complexes having functional groups were efficiently prepared, which are easily purified by silica-gel column chromatography. Selective click reactions were realized through the complexation of cycloalkynes with copper.